2015
DOI: 10.5897/ajps09.024
|View full text |Cite
|
Sign up to set email alerts
|

Hairy roots production in Phyllanthus odontadenius Mll. Arg. by seedlings transformed with Agrobacterium rhizogenes A4RS/pHKN29

Abstract: Phyllanthus odontadenius Müll. Arg is one of the most important medicinal plants in the genusPhyllanthus (Phyllanthaceae). It is used in different regions in the world for the treatment of various diseases for example malaria caused by Plasmodium falciparum causing millions deaths in tropical and subtropical regions. In this work, we experimented P. odontadenius seeds germination and seedlings infected by Agrobacterium rhizogenes A4RS/pHKN9. We obtained 36% of seeds that germinated for 84.6% of seedlings trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…odontadenius has been shown to have a strong antioxidant potential in the various studies carried out on the in vitro antioxidant activity of its various extracts used, thus corroborating its traditional uses [4,5]. The antioxidant potential of P. odontadenius would be explained in its composition in secondary metabolites previously analyzed by various authors and which was found to be rich in phenolic compounds [6,7,8]. Phytochemical and pharmacological studies carried out attest to success of P. odontadenius in therapy where the extracts of the twigs and leaves reveal antispasmodic, anticancer, antiplasmodial, antidysenteric, antifungal, analgesic properties, etc.…”
Section: Original Research Articlementioning
confidence: 87%
“…odontadenius has been shown to have a strong antioxidant potential in the various studies carried out on the in vitro antioxidant activity of its various extracts used, thus corroborating its traditional uses [4,5]. The antioxidant potential of P. odontadenius would be explained in its composition in secondary metabolites previously analyzed by various authors and which was found to be rich in phenolic compounds [6,7,8]. Phytochemical and pharmacological studies carried out attest to success of P. odontadenius in therapy where the extracts of the twigs and leaves reveal antispasmodic, anticancer, antiplasmodial, antidysenteric, antifungal, analgesic properties, etc.…”
Section: Original Research Articlementioning
confidence: 87%